Evaluación de riesgos laborales por puestos de trabajo en la planta de soldadura para la elaboración de matrices de riesgos bajo la norma GTC45 en la empresa CIAUTO. - Briceño Cárdenas, Alex Roberto (2019)
The purpose of this study is the evaluation of occupational risks, which was developed in the company "CIAUTO CIA LTDA." located in Ambato city, which does not have a risk assessment for working in the welding company because it is an enterprise that has been operating for a year, which is why a field investigation is carried out that leads to the identification and evaluation of occupational risks by job supports. The risks media were prepared under the Colombian Technical Guide GTC45, which has parameters in which we can measure the levels of probability, risks and consequences to which workers are exposed, resulting in the acceptability of the risk that may be acceptable, improvable, acceptable with control and not acceptable, in this way is how the risks were evaluated.At the welding company, physical, chemical, ergonomic, mechanical and electrical risks were identified, these being the most relevant risks, the same ones that through new studies could permanently minimize the problem.In this way the company performs compliance with legal requirements, ensuring the health of workers and the good performance of the production process. All the information collected will serve to perform the identification, analysis and evaluation of the jobs and implement action plans in the welding plant.